Global Impacts of Corruption Perception Index for the Attractiveness of Foreign Direct Investment - Mashrabjonovich, Ikboljon Odashev (New Innovations in Economics, Business and Management Vol. 4, 2022)
The article examines the correlation between the index of corruption perception and the index of the attractiveness of foreign direct investment in the formation and implementation of state investment policy and the impact of development projects of countries that carry out analytical formulas of multiple regression. And we recognize some important drivers and factors of modelling the problems of foreign direct investment, which associate with attracting into the economy, increasing the attractiveness of its development. At the main part of the investigation, it interpreters of econometric modeling of between the corruption degrees of selected countries and the attractiveness of foreign direct investment. The real examples are given related to corruption and foreign direct investment studied by different scientists of the world. The task is set on how it will determine how much corruption in the world will affect the attractiveness of foreign investors by selected countries.